Dialektika Positivisme dan Teori Kritis dalam Ilmu Sosial - Dida Maulidya Al Afshana; Agung Winarno; Subagyo Subagyo (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study examines the dialectic between positivism and critical theory as two major paradigms shaping the development of modern social science epistemology. Positivism, with its emphasis on objectivity, empirical verification, and causal laws, has become the foundation for systematic and measurable scientific research methods. However, the dominance of this paradigm has drawn criticism from critical theorists, highlighting positivism's limitations in understanding the historical, ideological, and power relations that influence social reality. This study aims to analyze the dialectical relationship between the two paradigms by examining their contributions, fundamental differences, and potential integration in the development of social science methodology. The method used is a conceptual-based literature review, through a review of relevant philosophical and methodological literature. The research findings indicate that positivism and critical theory not only represent paradigmatic opposition but also provide complementary opportunities for developing a more holistic approach to social research. Positivism plays a role in providing empirical rigor, while critical theory offers a reflective framework for understanding meaning, ideology, and power structures.